2023
DOI: 10.1073/pnas.2207355120
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in mutation spectra enhance access to beneficial mutations

Abstract: Biased mutation spectra are pervasive, with wide variation in the magnitude of mutational biases that influence genome evolution and adaptation. How do such diverse biases evolve? Our experiments show that changing the mutation spectrum allows populations to sample previously undersampled mutational space, including beneficial mutations. The resulting shift in the distribution of fitness effects is advantageous: Beneficial mutation supply and beneficial pleiotropy both increase, while deleterious load reduces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 70 publications
3
45
1
Order By: Relevance
“…This phenomenon also explains how mutator genotypes lacking mismatch repair can be indirectly selected for under conditions where mutation is necessary for cell survival, as the mutator genotypes are more likely to produce an adaptive mutation [138]. A recent study by Sane et al has also suggested that the change in mutational bias in mutator genotypes provides access mutational types that appear less often in wild-type backgrounds [11]. They argue that these under-sampled mutation types are more likely to be adaptive [11], therefore a change in mutation bias can be indirectly supported by a second-order selection effect.…”
Section: Future Work -Does Natural Selection Enforce Remove or Mostly...mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon also explains how mutator genotypes lacking mismatch repair can be indirectly selected for under conditions where mutation is necessary for cell survival, as the mutator genotypes are more likely to produce an adaptive mutation [138]. A recent study by Sane et al has also suggested that the change in mutational bias in mutator genotypes provides access mutational types that appear less often in wild-type backgrounds [11]. They argue that these under-sampled mutation types are more likely to be adaptive [11], therefore a change in mutation bias can be indirectly supported by a second-order selection effect.…”
Section: Future Work -Does Natural Selection Enforce Remove or Mostly...mentioning
confidence: 99%
“…With recent research revealing the impact of mutation bias on adaptation within the bacterial domain [10,11], there is an opportunity for microbiologists from various disciplines to consider what role mutation bias plays in the evolution of their organism(s) of interest. In this review, we will describe the features that cause mutation bias in bacterial genomes and discuss how we can use this knowledge to identify areas more prone to mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, a variety of studies have demonstrated interesting patterns of mutation across genomes that are pertinent to the rate and direction of evolutionary change. [67][68][69][70][71][72][73][74][75][76][77] One prominent example is the SOS system in bacteria, which has been presumed to increase the mutation rate across the entire genome (i.e., a form of hypermutability) in response to stress, speeding up the evolutionary search for adaptive solutions. [33,78] For some, such facultative modification of the mutation rate may seem in tension with one or both definitions of randomness.…”
Section: Objections: Modifier Theory Mutator Alleles and Hypermutabilitymentioning
confidence: 99%
“…One domain where this kind of experimental redesign could be fruitfully considered is in studies of mutation bias. [39,[68][69][70][100][101][102][103] Existing studies often focus simply on whether mutation rate variation has an impact on which loci undergo permanent genetic change, and thereby contributes to the "direction" of evolution. This impact is different than that of natural selection and random genetic drift on which alleles will go to fixation, and thus has been taken to suggest that mutation rate variation is a separate "force" of evolution.…”
Section: Ramifications: Revisiting a Classic Experimentsmentioning
confidence: 99%
“…Understanding what governs the occurrence of spontaneous mutations is crucial for predicting evolution [2][3][4]. Mutation rate is known to be influenced by genetic variation [5,6] and the environment [7][8][9] (i.e.…”
Section: Introductionmentioning
confidence: 99%